Traumatic Arterio-Enteric Fistula—A Report of 2 Cases With Review of Literature. (August 2021) - James, Joses Dany; Agarwal, Harshit; Kumar, Vignesh; Kumar, Atin; Hemachandran, Naren; Gupta, Amit
Background: Traumatic arterio-enteric fistula is predominantly seen after penetrating trauma with only 21 reported cases documented in the past 25 years. They may present in an acute or delayed manner with upper or lower gastrointestinal bleed. A detailed clinical examination with requisite imaging can help in detecting such injuries. Case Description: Case 1: A 20-year-old gentleman, presented with penetrating stab injury to the gluteal region with bleeding per rectum. Imaging revealed evidence of injury to the inferior rectal artery which was found to be communicating with the extraperitoneal portion of the rectum. He was managed with a combination of endovascular and open surgery with a successful outcome. Case 2: A 29-year-old gentleman, presented in a delayed manner 2 weeks after a gunshot wound to the gluteal region, which was managed operatively in another hospital. He developed a massive lower gastrointestinal bleed 2 weeks after presentation. Imaging revealed evidence of a pseudoaneurysm of the inferior gluteal artery which had a fistulous communication with the gastrointestinal tract leading to bleeding. It was managed by endovascular techniques successfully. Conclusion: Arterio-enteric fistulas following trauma are rare phenomena and they need a high index of suspicion for diagnosis. Once diagnosed, they can be managed based on their location and patient physiology by interventional techniques, surgery, or a combination of the two.